Mormonism's last colonizer: the life and times of William H. Smart - Smart, William B., author; Utah State University Press, publisher (Colorado State University. Libraries, 2008)
By the early twentieth century, the era of organized Mormon colonization of the West from a base in Salt Lake City was all but over. One significant region of Utah had not been colonized because it remained in Native American hands--the Uinta Basin, site of a reservation for the Northern Utes. When the federal government decided to open the reservation to white settlement, William H. Smart--a nineteenth-century Mormon traditionalist living in the twentieth century, a polygamist in an era when it was banned, a fervently moral stake president who as a youth had struggled mightily with his own sense of sinfulness, and an entrepreneurial businessman with theocratic, communal instincts--set out to ensure that the Uinta Basin also would be part of the Mormon kingdom.--Provided by publisher.
Growing up in Franklin -- Years of trial and torment -- An aborted mission -- A repentant sinner finds himself -- Putting a shoulder to the wheel -- On-the-job training in Heber Valley -- Making Indian land Mormon country -- The Vernal years -- Civilizing the reservation lands -- The fourth-and final-stake presidency -- Struggle and failure in Leota -- Hard times -- The final years.
Keywords: Mormons -- Utah -- Biography; Utah -- History; Smart, William H. (William Henry), 1862-1937